Average Economic Burden of Dementia in Slovenia and per Person in the Period 2019-2023 - Lovrečič, Mercedes; Lovrečič, Barbara (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Dementia is a widely recognized public health priority. The number of people with dementia will increase worldwide in the future, in parallel with demographic changes, life expectancy is increasing, and at the same time, the risk of dementia increases with aging. Dementia has a major economic impact on the patient, their relatives and society as a whole. Methods: We conducted a literature review regarding the economic costs of dementia and estimates of dementia prevalence. Results: Based on the selected methodology, we calculated the prevalence rate of dementia in Slovenia for the period 2019-2023, standardized by age and gender, and the costs of dementia in the period 2019-2023 and per person with dementia. Discussion: The burden of dementia represents a significant share of GDP and is increasing over the years, despite the high excess mortality during the COVID-19 pandemic. People with dementia, their relatives and caregivers need better support and financing of services. In 2019, the G20 summit committed to a common approach to dementia management with a declaration. Slovenia has adopted the Dementia Management Strategy in Slovenia until 2030 and a two-year Action Plan, which represent specific strategic documents for the implementation of activities and programs in the field of dementia. The economic and epidemiological assessments provided will help researchers, policymakers, healthcare professionals and other key stakeholders to better understand and address changes in the healthcare and social care environment.